2019
DOI: 10.3389/fcimb.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Competence in Streptococcus pneumoniae and Close Commensal Relatives: Mechanisms and Implications

Abstract: The mitis group of streptococci comprises species that are common colonizers of the naso-oral-pharyngeal tract of humans. Streptococcus pneumoniae and Streptococcus mitis are close relatives and share ~60–80% of orthologous genes, but still present striking differences in pathogenic potential toward the human host. S. mitis has long been recognized as a reservoir of antibiotic resistance genes for S. pneumoniae , as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 74 publications
1
71
0
Order By: Relevance
“…TCS05 inhibits the competence state [18][19][20][21], and promotes pneumococcal resistance to certain antibiotics and other stressful conditions [20,[22][23][24]. TCS12 activates the genes associated with the competence state and natural transformation [25][26][27]. TCS02 (WalR/K), the only TCS essential for pneumococcal viability, is associated with cell wall peptidoglycan metabolism [28,29]; TCS03 (LiaR/S) senses cell wall damage and inhibits autolysis [30], TCS04 (PnpR/S) regulates uptake of inorganic phosphate [31,32]; TCS06 (CbpR/S) activates expression of choline-binding protein A or PspC [33,34]; TCS08 is involved in the cellobiose uptake [35], production of pilus-1 [16] and surface protein PavB [16]; TCS13 (BlpR/H) regulates the production of bacteriocins (pneumocins) [36][37][38].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…TCS05 inhibits the competence state [18][19][20][21], and promotes pneumococcal resistance to certain antibiotics and other stressful conditions [20,[22][23][24]. TCS12 activates the genes associated with the competence state and natural transformation [25][26][27]. TCS02 (WalR/K), the only TCS essential for pneumococcal viability, is associated with cell wall peptidoglycan metabolism [28,29]; TCS03 (LiaR/S) senses cell wall damage and inhibits autolysis [30], TCS04 (PnpR/S) regulates uptake of inorganic phosphate [31,32]; TCS06 (CbpR/S) activates expression of choline-binding protein A or PspC [33,34]; TCS08 is involved in the cellobiose uptake [35], production of pilus-1 [16] and surface protein PavB [16]; TCS13 (BlpR/H) regulates the production of bacteriocins (pneumocins) [36][37][38].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Here, the application of Grad‐seq allowed us to identify the sedimentation profiles of thousands of S. pneumoniae transcripts and proteins simultaneously in a single experiment. We establish a use case for this complexome resource by uncovering an unexpected exonucleolytic stabilization of sRNAs in the competence regulon, a pathway essential for DNA uptake and important for pneumococcal virulence (Lin et al , ; Muschiol et al , ; Salvadori et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic relationship of both 16S rRNA and a core set of 136 genes indicated that this pathogen belongs to mitis group of Streptococcus (Kawamura et al, 1995;Richards et al, 2014). S. pneumoniae is capable of importing various genes including antimicrobial resistance genes via horizontal transfer from related species (Salvadori et al, 2019). In the United States of America, more than 30% of clinically isolated pneumococcal bacteria are resistant to one or more antibiotics (CDC, 2019).…”
Section: Introductionmentioning
confidence: 99%